The Development of an Information Society and Electronic Commerce in the European Union in the Context of Selected Documents of the EU and International Organisations; Rozwoj́ społeczenśtwa informacyjnego i handlu elektronicznego w Unii Europejskiej w konteksćie regulacji organizacji miedzynarodowych - Jacek Hibner (Comparative Economic Research. Central and Eastern Europe, 2012)
Due to the rapidly growing use of the Internet, the development of electronic commerce (defined by the World Trade Organization as "the production, distribution, marketing, sale or delivery of goods and services by electronic means"1) has become one of the key aspects of today's sustained growth. It influences productivity, facilitates the international movement of goods and services, and stimulates export and import trade. The European Union, as well as many multinational organisations, is working towards the harmonisation of their rules, and to facilitate and streamline this kind of international exchange. In this article, the author presents selected documents on electronic commerce published by the United Nations Commission on International Trade Law, the World Trade Organization, the Organisation for Economic Cooperation and Development, the International Chamber of Commerce and the European Union since 1994. – – W zwiazku z szybko pojawiajacymi sie nowymi sposobami korzystania z Internetu i rosnacym dostepem do niego na całym sẃiecie, rozwoj́ handlu elektronicznego (zdefiniowanego przez WTO jako "produkcje, dystrybucje, marketing, sprzedazi̇ dostawe dob́r i usług za pomoca komunikacji elektronicznej) stał sie jednym z kluczowych aspektoẃ zroẃnowazȯnego wzrostu. Handel elektroniczny wpływa na produktywnosć\', ułatwia miedzynarodowy przepływ dob́r i usług oraz stymuluje eksport i import tychzė. Unia Europejska i wiele organizacji miedzynarodowych od wielu lat pracuja nad harmonizacja prawa dotyczacego handlu elektronicznego oraz nad pobudzeniem i usprawnieniem tego typu wymiany miedzynarodowej. W niniejszym artykule autor prezentuje wybrane dokumenty dotyczace handlu elektronicznego opublikowane przez Komisje ONZ ds. Prawa Handlu Miedzynarodowego, Sẃiatowa Organizacje Handlu OECD, Miedzynarodowa Izbe Handlu oraz Unie Europejska od roku 1994.
Keywords: 330